2010
DOI: 10.1038/ng.583
|View full text |Cite
|
Sign up to set email alerts
|

A regulatory variant in CCR6 is associated with rheumatoid arthritis susceptibility

Abstract: Rheumatoid arthritis is a common autoimmune disease with a complex genetic etiology. Here, through a genome-wide association study of rheumatoid arthritis, we identified a polymorphism in CCR6, the gene encoding chemokine (C-C motif) receptor 6 (a surface marker for Th17 cells) at 6q27, that was associated with rheumatoid arthritis susceptibility and was validated in two independent replication cohorts from Japan (rs3093024, a total of 7,069 individuals with rheumatoid arthritis (cases) and 20,727 controls, ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
189
2
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 245 publications
(203 citation statements)
references
References 41 publications
4
189
2
2
Order By: Relevance
“…Even when a significant association of a variant was observed in multiple populations, the effect sizes and allele frequencies would not be identical between the populations. 90 Most of the recent studies have used metaanalysis assuming a fixed-effect model for effect sizes; however, metaanalysis assuming a random-effect model or other sophisticated methods is required for trans-ethnic studies. 91,92 Prioritization of GWAS results using external biological databases To effectively explore the genetic loci that were uncaptured by the standard GWAS approach, it would be important to assess the subloci of GWAS results by prioritizing or weighting them by incorporating information from external biological databases (Figure 2b).…”
Section: Meta-analysis Of Gwas Involving Multiple Populationsmentioning
confidence: 99%
“…Even when a significant association of a variant was observed in multiple populations, the effect sizes and allele frequencies would not be identical between the populations. 90 Most of the recent studies have used metaanalysis assuming a fixed-effect model for effect sizes; however, metaanalysis assuming a random-effect model or other sophisticated methods is required for trans-ethnic studies. 91,92 Prioritization of GWAS results using external biological databases To effectively explore the genetic loci that were uncaptured by the standard GWAS approach, it would be important to assess the subloci of GWAS results by prioritizing or weighting them by incorporating information from external biological databases (Figure 2b).…”
Section: Meta-analysis Of Gwas Involving Multiple Populationsmentioning
confidence: 99%
“…Moreover, mutations in CCR6 are also known to be responsible for other autoinflammatory disorders. For instance, the polymorphism rs3093024 in CCR6 associated with susceptibility to rheumatoid arthritis was observed in Japanese population (Kochi et al, 2010). Our case-control study, we finally found that T allele, TC/TT genotypes can significantly reduce susceptibility to digestive disorders in rabbit.…”
Section: Resultsmentioning
confidence: 57%
“…RA, in fact, responds to the definition of 'complex genetic disease'. A recent meta-analysis [78] conducted on Europeans has shown how complex the disease is by adding to the known susceptibility genes, 7 more, one of which is also shared by the Asian population [79]. These results have helped better characterize RA in the European and Asian population.…”
Section: A Case Study: Application To Immune Diseasesmentioning
confidence: 99%